Factors Influecing Financial Literacy; Analysis Of Helplessness, Cognition, Needs And Social Environment Moderation - Ade Maharini Adiandari; Putu Gede Denny Herlambang; Ni Nyoman Sudiyami; Nyoman Dwika Ayu Amrita (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to analyze the effect of cognition needs, feelings of Powerlessness, and moderation of the social environment on financial literacy. The methodology used is quantitative analysis with a structured survey of individuals aged 18-60 years. Data analysis was performed using Smart PLS SEM (Partial et al. – Structural Equation Modeling) software, which is efficient in handling latent variables and analyzing complex relationships between variables. The results of the hypothesis test showed that feelings of Powerlessness had a significant negative impact on financial literacy (coefficient -0.251, p < 0.001). In contrast, the influence of environmental moderation on feelings of Powerlessness on financial literacy was significantly positive (coefficient 0.104, p = 0.001). Cognition needs contribute significantly positively to literacy (coefficient 0.369, p < 0.001), but environmental moderation to Cognition needs shows no significant effect (coefficient -0.050, p = 0.238). Environmental variables themselves have a significant favorable influence on financial literacy (coefficient 0.289, p < 0.001). The conclusions of this study underscore the importance of understanding cognitive and environmental factors in efforts to improve financial literacy, as well as presenting a database for effective policy development and interventions.